2019
DOI: 10.1111/csp2.34
|View full text |Cite
|
Sign up to set email alerts
|

Land‐sharing potential of large carnivores in human‐modified landscapes of western India

Abstract: The current protected area (PA) network is not sufficient to ensure long‐term persistence of wide‐ranging carnivore populations. Within India, this is particularly the case for species that inhabit nonforested areas since PAs disproportionately over‐represent forested ecosystems. With growing consideration of human‐use landscapes as potential habitats for adaptable large carnivores, India provides a model for studying them in densely populated landscapes, where there is little understanding about human‐carnivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 77 publications
(127 reference statements)
1
24
1
Order By: Relevance
“…But we posit that it may be a scale-dependent effect; at finer spatial scales, agricultural areas likely serve as secondary habitats, offer temporary refuges, and facilitate connectivity for these carnivores (Vanak & Gompper 2010; Athreya et al 2015; Majgaonkar et al 2019). Changes in crop type, transitions from seasonal to year-round cultivation, expansion of permanent irrigation, and intensification of pesticide use (impacting lower trophic levels) could create altered landscapes (UNCCD 2017), leading to local extinctions and/or shifts in carnivore communities (e.g., Majgaonkar et al 2019). Future studies will need to undertake detailed investigations on these aspects to offer deeper ecological insights and augment our findings.…”
Section: Discussionmentioning
confidence: 99%
“…But we posit that it may be a scale-dependent effect; at finer spatial scales, agricultural areas likely serve as secondary habitats, offer temporary refuges, and facilitate connectivity for these carnivores (Vanak & Gompper 2010; Athreya et al 2015; Majgaonkar et al 2019). Changes in crop type, transitions from seasonal to year-round cultivation, expansion of permanent irrigation, and intensification of pesticide use (impacting lower trophic levels) could create altered landscapes (UNCCD 2017), leading to local extinctions and/or shifts in carnivore communities (e.g., Majgaonkar et al 2019). Future studies will need to undertake detailed investigations on these aspects to offer deeper ecological insights and augment our findings.…”
Section: Discussionmentioning
confidence: 99%
“…While land sharing is increasingly being recognized as vital to carnivore persistence within human-modified landscapes (Chapron et al 2014, Stephens 2015, operationalizing this concept has been complicated by a limited understanding of carnivore ecology within agroecosystems. While many studies on large carnivore use of human-modified areas exist (Woodroffe 2011, Boron et al 2018, Majgaonkar et al 2019, there remain critical gaps in our understanding of carnivore ecology within agricultural areas. In a review of carnivore use of agroecosystems, Ferreira et al (2018) found that the extent to which agricultural areas offer foraging habitats, dispersal routes, or cover for large carnivores remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, White, Jennings, Renwick, & Barker, 2005 cautioned that an interview-based approach should (a) minimize the number of nonrespondents, and (b) quantify the bias arising from nonresponse. Majgaonkar et al (2019) have interviewed 4.5 ± 3.4 (SD) persons per sampling unit, ranging from 1 to 18 respondents. When data are sparse, occupancy models are known to produce unstable results, which include boundary estimates producing the fitted probability of 0 or 1 (Welsh, Lindenmayer, & Donnelly, 2013).…”
mentioning
confidence: 99%
“…When data are sparse, occupancy models are known to produce unstable results, which include boundary estimates producing the fitted probability of 0 or 1 (Welsh, Lindenmayer, & Donnelly, 2013). For example, the Indian wolf occupancy map of Majgaonkar et al (2019) exhibits this issue clearly where most of the sites have fitted a very high occupancy probability. With such uniform probability distribution, any prioritization of conservation sites is not possible.…”
mentioning
confidence: 99%
See 1 more Smart Citation